2020
DOI: 10.1155/2020/6959741
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Inhibits LPS-Induced NLRP3 Inflammasome Priming in Macrophages by Suppressing Xanthine Oxidase

Abstract: Following traumatic insult and associated pathogen infection, innate immunity is activated during the perioperative period, especially the NLRP3 inflammasome in macrophages. The neuroendocrine response is also rapidly activated to regulate excessive inflammation; however, the molecular mechanisms are still not completely clear. This study is aimed at investigating the modulation of NLRP3 inflammasome priming by endogenous glucocorticoids (corticosterone, CORT) and its relationship with xanthine oxidase (XO). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…This result suggests that BITC inhibits the IL-1β production by suppressing the P. aeruginosa LPS-induced signaling pathways. Several studies have reported that LPS stimulates IL-1β production through the activation of inflammasomes [30,31]. In this regard, we investigated whether BITC inhibits the activation of inflammasomes such as NLRP3 and caspase-1 in the cytosol.…”
Section: Discussionmentioning
confidence: 98%
“…This result suggests that BITC inhibits the IL-1β production by suppressing the P. aeruginosa LPS-induced signaling pathways. Several studies have reported that LPS stimulates IL-1β production through the activation of inflammasomes [30,31]. In this regard, we investigated whether BITC inhibits the activation of inflammasomes such as NLRP3 and caspase-1 in the cytosol.…”
Section: Discussionmentioning
confidence: 98%
“…Whether the P2X7 receptor can also trigger cytokine upregulation and release independent of IL-1β is less well studied. This is relevant as the NLRP3 inflammasome requires "priming" to increase expression of key components, such as NLRP3 itself, before the activation stage can occur [6], and priming of inflammasome components may be rate-limiting in chronic age-dependent diseases [7]. The involvement of the P2X7 receptor in release of cytokines other than IL-1β may thus have implications for earlier stages in chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In all the above behavioral studies, we used LPS as a correlate to induce NLRP3-mediated inflammasome, , and the results obtained were similar to those of the MCAO treated groups. The recovery of behavioral function in Sham and MCAO rats was shown to be comparable across the functional outcomes.…”
Section: Resultsmentioning
confidence: 62%